General practitioners’ stay-at-work practices in patients with musculoskeletal disorders: using Intervention Mapping to develop a training program - A. Møller; C. B. Bond; L. N. Andersen; J. Hartvigsen; M. J. Stochkendahl (Scandinavian Journal of Primary Health Care, 2023)
Objectives To describe current stay-at-work practices among Danish general practitioners (GPs) in relation to patients with musculoskeletal disorders, to identify potential avenues for improvement, and to suggest a training program for the GPs.Design and Setting We followed the principles of Intervention Mapping. Data were collected by means of literature searches, focus group interviews with GPs, and interaction with stakeholder representatives from the Danish labour market.Results GPs’ current stay-at-work practices were influenced by systemic, organisational, and legislative factors, and by personal determinants, including knowledge and skills relating to stay-at-work principles and musculoskeletal disorders, recognition of the patient’s risk of long-term work disability, their role as a GP, and expectations of interactions with other stay-at-work stakeholders. GPs described themselves as important partners and responsible for the diagnostic and holistic assessments of the patient but placed themselves on the side line relying on the patient or workplace stakeholders to act. Their practices are influenced both by patients, employers, and by other stakeholders. We propose a training course for GPs that incorporate both concrete tools and behaviour change techniques.Conclusions We have identified varied perspectives on the roles and responsibilities of GPs, as well as legislative and organisational barriers, and proposed a training program. Not all barriers identified can be addressed by a training course, and some questions are left unanswered, among others - who are best suited to help patients staying at work?